A phase II study of combined therapy with a BRAF inhibitor (vemurafenib) and interleukin-2 (aldesleukin) in patients with metastatic melanoma - Meghan J. Mooradian (OncoImmunology, 2018)
Background: Approximately 50% of melanomas harbor BRAF mutations. Treatment with BRAF +/− MEK inhibition is associated with favorable changes in the tumor microenvironment thus providing the rationale for combining targeted agents with immunotherapy. Methods: Patients with unresectable Stage III or IV BRAFV600E mutant melanoma were enrolled in a single-center prospective study (n = 6). Patients were eligible to receive two courses of HD-IL-2 and vemurafenib twice daily. The primary endpoint was progression-free survival (PFS) with secondary objectives including overall survival (OS), response rates (RR), and safety of combination therapy as compared to historical controls. Immune profiling was performed in longitudinal tissue samples, when available. Results: Overall RR was 83.3% (95% CI: 36%–99%) and 66.6% at 12 weeks. All patients eventually progressed, with three progressing on treatment and three progressing after the vemurafenib continuation phase ended. Median PFS was 35.8 weeks (95% CI: 16–57 weeks). Median OS was not reached; however, the time at which 75% of patients were still alive was 104.4 weeks. Change in circulating BRAFV600E levels correlated with response. Though combination therapy was associated with enhanced CD8 T cell infiltrate, an increase in regulatory T cell frequency was seen with HD-IL-2 administration, suggesting a potential limitation in this strategy. Conclusion: Combination vemurafenib and HD-IL-2 is well tolerated and associated with treatment responses. However, the HD-IL-2 induced increase in Tregs may abrogate potential synergy. Given the efficacy of regimens targeting the PD-1 pathway, strategies combining these regimens with BRAF-targeted therapy are currently underway, and the role of combination vemurafenib and HD-IL-2 is uncertain. Trial Registration: Clinical trial information: NCT01754376; https://clinicaltrials.gov/show/NCT01754376